The Misinformation Pandemic: Battling the Real Threat from Covid-19 - Ramlachan, Nicole; Muhammad, Mujahidah (British Journal of Healthcare and Medical Research, 2023)
The World Health Organization declared Covid-19 pandemic a public health emergency in Jan 2020 to May 2023, with 770 million confirmed cases and 7 million deaths worldwide; considered highly underreported especially in countries without genomic surveillance data. The COVID-19 pandemic has not only prompted serious health challenges, but it has also resulted in an abundance of misinformation and misconceptions, especially regarding COVID-19 vaccines. The debate emphasizes the importance of evidence-based communication techniques and actions to counteract COVID-19 misinformation and misconceptions. The pandemic of COVID-19 has highlighted the essential importance of trustworthy data in public health measures. Along with scientific advances and public health efforts, there has been an exceptional increase in misinformation and misconceptions about the pandemic, particularly regarding COVID-19 vaccines and the origin of the pandemic. The article will look at the origins, propagation, and effects of misinformation about COVID-19 vaccinations and pandemic fabrications, providing insights into the underlying dynamics and public health concerns. We investigate sources and generation of misinformation surrounding COVID-19 vaccinations, origin conspiracy theories and pandemic fabrications on social media to present a thorough analysis of its impact, as well as the repercussions of misconceptions on public health efforts. Contributing associated deaths/hospitalizations from the infodemic due to unsanctioned cure/preventatives due by rumor, stigma and conspiracy theories related to COVID-19 are unknown. The anti-vax campaign against Covid-19 vaccination, rumors, stigma, and conspiracy theories can decrease trust in governments and international health agencies, create hesitancy and lead to serious impact on health systems. This study highlights false information disseminated during the COVID-19 pandemic and discusses sources of misinformation and its implications. A review of social media posts contributing to vaccine hesitancy, spread of COVID-19 and high mortality rates was performed. Results show influences from various social media rumours and conspiracy theories increased vaccination hesitancy. Caribbean region has lower immunization rates, in part due to misconceptions spread during the infodemic stage. Efforts should be made to gain trust, debunk misinformation, prevent early-onset misinformation infodemics and increase adherence to health guidelines in times of public health emergencies to reduce associated deaths and limit impact on non-adherence to other public health guidelines such as childhood vaccinations.